Perspektif Keberhasilan Pendidikan Tinggi: Ikhtiar Mencari Strategi Untuk Pengembangan Pendidikan Tinggi Islam - Baharuddin Baharuddin (UIN Maulana Malik Ibrahim Malang, 2000)
The selection of universities still seems to be a problematic issue. Because until now, the variables to measure whether higher education institutions, especially PTI, are successful and reliable as a vehicle and means to foster and simulate their next generation is still and will remain questionable extension. Especially when the issue of